Civil Commitment for Substance Use Disorders: Coercion or Compassion? - Geppert, Cynthia M. A. (Psychiatric Times, 2022)
The article addresses clinical ethics arguments for and against civil commitment for substance use disorders (SUDs). Topics discussed include legal basis of civil commitment, explanation on civil commitment for SUD in state law, and ethical analysis and recommendations about civil commitment for SUD.